Istikhdām Tathbĩq Bupin Kawasĩlah Ta’lĩmiyyah Raqmiyyah Fĩ Tadrĩs Al Lughah Al ‘Arabiyyah - Yastin Nadia, Renda; Farid, Edi Kurniawan; Sofa, Ainur Rofiq (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
This study discusses the use of the Bupin application in learning the Arabic language for grade VIII students at the NU Kraksaan Islamic Tsanawiyah madrasah. The Bupin application provides interactive features such as learning videos and QR code-based visual materials, which make learning more engaging and easy to understand. We collected data using descriptive qualitative research methods through interviews, observations, and documentation. This research illustrates how the Bupin app supports students' focus, motivation, and engagement in the learning process. Teachers also feel the benefits of this application because it helps deliver material creatively.  However, there are some technical constraints, such as limited devices and internet access, which pose challenges to implementing this application. Bupin enriches the modern learning process by providing a more interactive learning experience and supporting students' understanding of the concepts taught. This research encourages the development of school facilities and teacher training so that the Bupin application can be optimally utilized in Arabic language learning at Madrasah Tsanawiyah Islamiyah NU Kraksaan.